Vice and Virtue Behaviors: Disentangling Substitution and Direct Effects of the Price of Giving - Alexander D. Cornish; Stephanie A. Heger (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine how the U.S. tax policy that encourages charitable giving also affects seemingly unrelated virtue and vice behaviors: exercise and smoking. Using the Panel Study of Income Dynamics, we calculate tax liabilities for 16,712 individuals over 5 waves from which we can construct the price of giving to charity. We estimate the structural model of joint consumption developed by DiNardo and Lemieux (1992, 2001) to disentangle how changes in the price of giving affects exercise and smoking through two distinct channels:(1) an indirect effect through classical substitution effects and (2) a direct effect of the price of giving on the implicit price of exercise and smoking. Contrary to reduced form results which confound these two effects, we find that charitable giving and exercise are substitutes, but that the negative direct effect of the price of giving on exercise dominates. Similarly, charitable giving and smoking are also substitutes, but there is no significant direct effect of the price of giving on smoking behavior. Our results demonstrate the breadth of the effects of tax policy on charitable giving and suggest how policy may be more efficiently designed to increase virtuous behaviors.
Keywords: 330